Organic solvent poisoning: Case report - Trifunović Slobodan; Teovanović Dragana; Radičević Branko (ABC: časopis urgentne medicine, 2016)
INTRODUCTION: Organic solvents are chemical compounds used across various industries as well as in the household and are therefore easily accessible to most people. One of the most commonly used organic solvents is the nitro thinner, widely used to dilute nitro coatings especially in the automotive industry. This type of poisoning is mostly accidental, although there have been cases of deliberate self injury. The compound is most commonly absorbed by inhalation, but can also be absorbed through skin contact after the compound is directly exposed to the organism. The predominant symptomatology of the poisoning is shown in the CNS. Acute poisoning caused by mild concentrations result in headaches, vertigo, nausea, and confusion while larger concentrations can result in a CNS depression that can lead to a comma or respiratory arrest. AIM: A display of a case of acute organic solvent poisoning. MATERIALS AND METHODS: The source of the data are the ER patient protocols and anamnesis obtained through the anesthesiology ward of Loznica General Hospital. The results were obtained through a retrospective data analysis. CASE REPORT: Subject was a 24-year old male admitted to the infirmary after complaining about a consciousness disorder. The patient was somnolent during the examination. BP - 120/80 mmHg, ECG - sinus rhythm, P around 95/min, normogram, no significant ST and T changes, clear heart tones, respiratory sounds diffusely weakened over both hemithoracis, SaO2 92%. The intravenous line was secured and the patient received a crystalloid solution infusion and an oxygen therapy through a nasal mask. During transport to the pulmonology ward the patient had experienced a deterioration of consciousness and fell into a coma followed by tonic-clonic seizures of the extremities. The patient was urgently transferred to the anesthesiology ward where he was intubated and sent to the toxicology ward of the Military Medical Academy of Belgrade. There he received a detoxification treatment and was stabilized. CONCLUSION: Organic solvent poisoning shows a severe clinical picture and is very rare but occurs with specialized occupations. Because of a potential fatal outcome these cases have to be successfully diagnosed in spite of scarce medical history. It is imperative to properly diagnose the poisoning, commence corresponding initial therapy and transport the properly prepared patient to an adequate health facility.